2007
DOI: 10.2174/138920007779315026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phenobarbital on Morphine Metabolism and Disposition:LC-MS/MS Determination of Morphine (M) and Morphine-3-Glucuronide (M3G) in Wistar-Kyoto Rat Serum, Bile, and Urine

Abstract: A simple LC-MS/MS method has been developed and validated for the simultaneous determination of morphine (M) and morphine-3-glucuronide (M3G) in rat serum, bile, and urine. Deuterated D3-M and D3-M3G were used as internal standards (IS) for M and M3G, respectively. Serum samples were processed by acetonitrile precipitation. Bile samples were prepared by solid-phase extraction (SPE) using Oasis MCX cartridges. Urine samples were directly analyzed after dilution with mobile phase. Chromatography was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 50 publications
(59 reference statements)
1
14
0
Order By: Relevance
“…In more recent studies, serum M3G AUC values were also reported to be approximately twofold higher in female compared with male Wistar rats. 25 Morphine-3-glucuronide has been shown previously to act supraspinally to attenuate morphine antinociception. 26 Hence, higher circulating M3G concentrations in female compared with male rats following acute morphine administration would be expected to result in greater attenuation of morphine antinociception in female compared with male rats in the hot plate test, consistent with the experimental observations reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…In more recent studies, serum M3G AUC values were also reported to be approximately twofold higher in female compared with male Wistar rats. 25 Morphine-3-glucuronide has been shown previously to act supraspinally to attenuate morphine antinociception. 26 Hence, higher circulating M3G concentrations in female compared with male rats following acute morphine administration would be expected to result in greater attenuation of morphine antinociception in female compared with male rats in the hot plate test, consistent with the experimental observations reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…The glucuronides of morphine are one of the most important reactive phase II metabolites, with their importance lying in the fact that morphine-3-O-glucuronide is an inactive metabolite, whereas morphine-6-O-glucuronide possesses pharmacological activity greater than that of the parent compound. Therefore, numerous quantitative LC/MS methods have been developed for the simultaneous detection of morphine, M3G, and M6G in human urine [149][150][151] plasma [141][142]150,152], and meconium [21], rat plasma and hair [153], bile and urine [154], whole blood and brain tissue [155], and dog and monkey plasma [156]. M3G is a typical opiate monitored in the confirmatory analysis for multiple drugs of abuse in plasma and urine [73,157].…”
Section: Quantitative Lc/ms Analysismentioning
confidence: 99%
“…Morphine is the most commonly-used opiate analgesic for the treatment of severe pain [1,2]. In humans, the major metabolites of morphine are morphine-3b-glucuronide (M3G) and morphine-6b-glucuronide (M6G) [3 -5].…”
Section: Introductionmentioning
confidence: 99%
“…Both of these metabolites are pharmacologically active, but have opposite effects. The effects of M6G have been reported to be equal to or greater than morphine [6 -8], while M3G counteracts morphine's analgesic activity [1,6]. Published reports have shown that these glucuronide metabolites may be formed in different amounts in other animals that may be used in pharmacokinetic or pharmacodynamic drug studies [9 -15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation